A Study on the General Public’s Perceptions of Dental Fear Using Unstructured Big Data - Han-A Cho; Bo-Young Park (치위생과학회지, 2023)
Background: This study used text mining techniques to determine public perceptions of dental fear, extracted keywords related to dental fear, identified the connection between the keywords, and categorized and visualized perceptions related to dental fear.Methods: Keywords in texts posted on Internet portal sites (NAVER and Google) between 1 January, 2000, and 31 December, 2022, were collected. The four stages of analysis were used to explore the keywords: frequency analysis, term frequency-inverse document frequency (TF-IDF), centrality analysis and co-occurrence analysis, and convergent correlations. Results: In the top ten keywords based on frequency analysis, the most frequently used keyword was ‘treatment,’ followed by ‘fear,’ ‘dental implant,’ ‘conscious sedation,’ ‘pain,’ ‘dental fear,’ ‘comfort,’ ‘taking medication,’ ‘experience,’ and ‘tooth.’ In the TF-IDF analysis, the top three keywords were dental implant, conscious sedation, and dental fear. The co-occurrence analysis was used to explore keywords that appear together and showed that ‘fear and treatment’ and ‘treatment and pain’ appeared the most frequently. Conclusion: Texts collected via unstructured big data were analyzed to identify general perceptions related to dental fear, and this study is valuable as a source data for understanding public perceptions of dental fear by grouping associated keywords. The results of this study will be helpful to understand dental fear and used as factors affecting oral health in the future.